To expand the expression \((−3x−1)(2x^2−x−2)\), we will use the distributive property (also known as the FOIL method for binomials, but we’ll apply it to a trinomial).
-
Begin by distributing \(-3x\) to each term in the second polynomial \(2x^2 − x − 2\): \[ -3x \cdot 2x^2 = -6x^3 \] \[ -3x \cdot (-x) = 3x^2 \] \[ -3x \cdot (-2) = 6x \]
So, combining these results gives: \[ -6x^3 + 3x^2 + 6x \]
-
Next, distribute \(-1\) to each term in the polynomial \(2x^2 − x − 2\): \[ -1 \cdot 2x^2 = -2x^2 \] \[ -1 \cdot (-x) = x \] \[ -1 \cdot (-2) = 2 \]
So, combining these results gives: \[ -2x^2 + x + 2 \]
-
Now, we can combine all the results from both distributions: \[ -6x^3 + (3x^2 - 2x^2) + (6x + x) + 2 \]
-
Simplify by combining like terms: \[ -6x^3 + (3x^2 - 2x^2) = -6x^3 + 1x^2 \] \[ (6x + x) = 7x \]
Hence, we get the combined polynomial: \[ -6x^3 + x^2 + 7x + 2 \]
-
Finally, write the polynomial in standard form: \[ -6x^3 + x^2 + 7x + 2 \]
Thus, the expanded expression in standard form is: \[ \boxed{-6x^3 + x^2 + 7x + 2} \]